GLACIOLOGICAL DATA COLLECTED BY THE JAPANESE ANTARCTIC RESEARCH EXPEDITION IN 1980 - KOBAYASHI, Shun'ichi; OHATA, Tetsuo; ISHIKAWA, Nobuyoshi; MATSUBARA, Kouji; KAWAGUCHI, Sadao (National Institute of Polar Research, 1982)
P(論文) departmental bulletin paper